A sugar-responsive liposome, an oriented electrospun membrane for bone regeneration in a diabetic environment and a preparation method thereof

CN117547511BActive Publication Date: 2026-10-27THE FIRST AFFILIATED HOSPITAL OF SOOCHOW UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202311338375.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-10-16
Publication Date
2026-10-27
Estimated Expiration
2043-10-16

AI Technical Summary

Technical Problem

然而,DM微环境通常伴随着血糖水平的波动,这进一步延长了促炎表型(M1)巨噬细胞的局部停留时间,并显著延迟了M2巨噬细胞的产生,进一步加重炎症并导致骨修复过程中的损伤

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure HDA0004496473750000011
    Figure HDA0004496473750000011
  • Figure HDA0004496473750000012
    Figure HDA0004496473750000012
Patent Text Reader

Abstract

The application discloses a sugar-responsive liposome, an oriented electrospun film for bone regeneration in a diabetic environment and a preparation method of the oriented electrospun film. The oriented electrospun film comprises an oriented nanofiber scaffold and a self-assembled substance compounded by the oriented nanofiber scaffold, and the self-assembled substance is formed by collagen and a sugar-responsive liposome preparation. The PCLA oriented electrospun film and the like of the embodiment of the application remodels a pathological diabetic microenvironment into a regeneration microenvironment by blocking an IRE alpha / NOD-like / NF kappa B signal path, reprograms the transformation of macrophages from an M1 phenotype to an M2 phenotype, and enhances osteogenic differentiation and angiogenesis. In general, the obtained findings show that the PCLA regulates an immune microenvironment and enhances the osseointegration of a bone periosteal defect of a diabetic patient. In addition, the research provides an effective strategy for designing a functionalized biomaterial used for bone regeneration treatment of a diabetic patient.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of bone regeneration, specifically involving methods for preparing glucose-responsive liposomes, preparing ordered spinning, and self-assembling of type I collagen. Among them are: a liposome material with glucose-responsive groups, an oriented electrospun membrane for spatiotemporal immune regulation and / or bone vascular regeneration in diabetic environments, and its preparation method. Background Technology

[0002] Diabetes mellitus (DM) is a long-term metabolic disorder affecting 425 million people worldwide in 2017, and this number is estimated to exceed 629 million by 2035. In addition to well-known macrovascular and microvascular complications such as stroke, retinopathy, neuropathy, and nephropathy, people with diabetes have a higher risk of fractures than healthy individuals. This is associated with their disordered glucose metabolism and increased levels of underlying inflammation, which can increase the risk of fractures by 20-300%. Normally, the periosteum contributes to over 70% of bone and cartilage formation in the early stages of fracture healing. However, in the DM microenvironment, excessive accumulation of chronic inflammation and advanced glycation end products (AGEs), along with the presence of reactive oxygen species, can impair the activation and differentiation of mesenchymal stem cells. This leads to weakened osteogenic differentiation, reduced angiogenesis, and exacerbated poor periosteal healing, ultimately resulting in nonunion of bone defects. Therefore, periosteal regeneration strategies for patients with diabetes must be re-examined.

[0003] Currently, many methods exist to improve bone healing, including drugs, growth factors, ultrasound, lasers, and pulsed electromagnetic fields; however, insufficient bone formation and the inability to accurately and controllably release growth factors limit the application of these methods. In addition, bone repair materials can be used as adjunctive therapy, but traditional bone repair materials primarily focus on optimizing osteogenesis. They typically use inert materials to avoid immune rejection, neglecting the essential function of the immune system in tissue repair and regeneration. Ignoring immune regulation and focusing solely on bone induction often fails to adapt to the pathological microenvironment.

[0004] As a primary defense mechanism of the innate system, macrophages possess an anti-inflammatory and therapeutic phenotype (M2), which can alleviate inflammation and provide a beneficial immune microenvironment for bone regeneration. However, the DM microenvironment is often accompanied by fluctuations in blood glucose levels, which further prolongs the local residence time of pro-inflammatory phenotype (M1) macrophages and significantly delays the production of M2 macrophages, further exacerbating inflammation and leading to damage during bone repair. Therefore, the dynamic transition from the M1 to M2 phenotype is difficult to achieve under chronic inflammatory conditions. In conclusion, the rational design of bone repair materials that can dynamically respond to changes in blood glucose levels and possess multiple functions such as immunomodulation and osteoinduction is of great significance for promoting bone healing in diabetic patients. Such materials hold promise for providing more effective treatment strategies and improving bone health and functional recovery. Summary of the Invention

[0005] In view of this, the present invention provides a sugar-responsive liposome, an oriented electrospun membrane for bone regeneration in a diabetic environment, and a method for preparing the same. The oriented electrospun membrane provided by the present invention is a composite functional scaffold material that can regulate immune function in a fluctuating high glucose inflammatory microenvironment, achieve a relatively stable and favorable osteogenic microenvironment, facilitate the effective design of functionalized biomaterials, and be used for bone regeneration treatment in diabetic patients.

[0006] This invention provides a sugar-responsive liposome, prepared from phospholipids, cholesterol, and fluorophenylboronic acid grafts, wherein the fluorophenylboronic acid graft is a phospholipid-p-fluorophenylboronic acid graft or a cholesterol-p-fluorophenylboronic acid graft.

[0007] In embodiments of the present invention, the fluorophenylboronic acid graft is one or more of DSPE-PEG-FPBA, DPPE-PEG-FPBA and DOPE-PEG-FPBA, preferably DSPE-PEG-FPBA; the molecular weight of the PEG segment in the fluorophenylboronic acid graft is preferably 1000-3000.

[0008] In an embodiment of the present invention, the mass ratio of phospholipids, cholesterol and fluorophenylboronic acid grafts in the raw materials for preparing sugar-responsive liposomes is 40:10:1 to 4.

[0009] This invention provides a glucose-responsive liposome formulation, comprising: the glucose-responsive liposome described above, and an immunomodulator encapsulated thereon, wherein the immunomodulator is preferably APY29. Specifically, the release rate of the immunomodulator in the glucose-responsive liposome formulation is positively correlated with the glucose concentration.

[0010] This invention provides an oriented electrospun membrane for bone regeneration in diabetic settings, comprising an oriented nanofiber scaffold and a self-assembled material thereof, wherein the self-assembled material is formed from collagen and the sugar-responsive liposome formulation described above; the collagen is preferably type I collagen.

[0011] In embodiments of the present invention, the material of the oriented nanofiber scaffold is one or more of PLA, PCL and PCLA, preferably PLA.

[0012] In an embodiment of the present invention, the average fiber diameter of the oriented nanofiber scaffold is 0.8-1.3 μm, and the oriented electrospun membrane is hydrophilic, with a water contact angle preferably 32°-100°, more preferably 35-80°.

[0013] This invention provides a method for preparing an oriented electrospun membrane for bone regeneration in diabetic settings, comprising the following steps:

[0014] S1. Nanofibers with different orientations were prepared by electrospinning, and the oriented nanofiber membranes were collected. The sugar-responsive liposome formulations mentioned above were prepared by reverse evaporation.

[0015] S2. The sugar-responsive liposome preparation and collagen solution are mixed and placed on the oriented nanofiber membrane, and the oriented electrospun membrane is obtained by self-assembly.

[0016] In an embodiment of the present invention, in step S2, the collagen solution is neutral and the solute is type I collagen; the self-assembly temperature is 35-38°C and the time is more than 30 minutes.

[0017] See Figure 1 and Figure 2 This invention addresses the critical issues of the adverse effects of chronic inflammatory microenvironment on periosteal repair under diabetic pathological conditions and the dynamic adjustment of the osteogenic microenvironment by blood glucose fluctuations. It designs and prepares a liposome surface-modified material with glucose-responsive groups, along with collagen self-assembly and electrospinning, to gradually construct a biomimetic microenvironment-responsive fiber repair material. Firstly, Figure 1 The diagram illustrates sugar-responsive liposomes and their preparation, as well as the construction of a time-regulated immune and osteogenic angiogenesis complex, including a technical solution utilizing surface modification of liposomes with sugar-responsive groups and a type I collagen self-assembly strategy. Secondly, Figure 2 The functional characterization verification is illustrated. The embodiments of the present invention verify the ability of the composite material system to regulate immunity and osteogenic and angiogenesis, as well as the therapeutic effect of the system on periosteal defects in diabetic rats.

[0018] The pathological diabetic microenvironment, characterized by glucose fluctuations and chronic inflammation, leads to delayed healing of periosteal defects. Therefore, it is necessary to develop novel materials that promote bone integration and are suitable for use in the complex microenvironment of diabetes. This application investigates a novel glucose-responsive fibrous scaffold composite material that modulates the local immune microenvironment and promotes bone integration at the periosteal-implant interface.

[0019] Among them, micro / nanoparticle-based glucose-responsive drug delivery systems are promising therapeutic drug delivery strategies. For example, liposomes have been endowed with stimulus-responsive features that can trigger the complete release of encapsulated drug molecules. When the surface membrane of the liposome becomes porous, the contents of the liposome start to leak, which in turn leads to a further decrease in membrane tension and eventual rupture. In the DM microenvironment, high glucose concentration can promote endogenous stimulation and change the structural state of liposomes. Phenylboronic acid (PBA) is a common glucose-responsive component, which has good structural stability and flexibility in addition to being easy to prepare at a low price. In addition, PBA can bind to the hydroxyl groups at the 1,2 or 1,3 positions of glucose to form a dynamic borate structure. This reaction causes the PBA molecule to be negatively charged. This negative charge endows PBA with further chemical properties and reactivity, giving it the potential to modify positively charged liposomes. However, due to the diverse structures of boronic acid formed under different acidities, where the pKa of PBA ranges from 7.8 to 8.6, the stability of the borate formed by this modification method is poor. More specifically, in a physiological environment (pH 7.4 < pKa, the neutral environment of the human body), PBA transforms into an uncharged planar structure, which is difficult to react with hydroxyl groups and less likely to bind to glucose. This results in glucose borate being unstable and prone to hydrolysis, thereby causing low glucose responsiveness.

[0020] In contrast, the present invention provides a liposome material surface-modified with glucose-responsive groups, wherein a fluorophenylboronic acid graft (containing -FPBA) is modified in the liposome structure. In the present application, an electrophilic group is introduced into PBA to generate 4-fluorophenylboronic acid (FPBA) with a pKa reduced to 7.2. Using this strategy, the negative charge generated by the binding of glucose and FPBA will cause FPBA to change from hydrophobic to hydrophilic. Therefore, glucose should bind to the FPBA units on the liposome membrane, which will lead to structural transformation and swelling of the membrane. Eventually, the liposome should release the loaded drug or other factors.

[0021] The examples of the present application use a substance obtained by grafting FPBA to phospholipid or cholesterol (i.e., phospholipid p-fluorophenylboronic acid graft or cholesterol p-fluorophenylboronic acid graft) to directly prepare the glucose-responsive liposome with the raw materials for liposome preparation, so that the FPBA group acts as a modifying group to modify the liposome. Further, the present application selects to combine FPBA with phosphatidylethanolamine-polyethylene glycol to form PE-PEG-FPBA, which serves as the modifying group for modifying the liposome; the advantage lies in that this modification technology is relatively mature, and the modified liposome material is relatively stable and will not affect the liposome's loading of drug preparations and the like.

[0022] Liposomes are artificial membranes; in water, the hydrophilic heads of phospholipid molecules insert into the water, while the hydrophobic tails of the liposomes extend into the air, forming spherical liposomes with a lipid bilayer upon agitation. The pharmaceutical definition of liposomes refers to microvesicles formed by encapsulating drugs within a lipid bilayer. The raw materials for liposome preparation include phospholipids and cholesterol; cholesterol can strengthen the lipid bilayer membrane, reduce membrane flow, and decrease leakage. Phospholipids include natural and synthetic phospholipids. Natural phospholipids are mainly lecithin (phosphatidylcholine, PC), which is neutral, while synthetic phospholipids include DSPE (distearylphosphatidylethanolamine), DPPE (dispalmitoylphosphatidylethanolamine), and DOPE (dioleoylphosphatidylethanolamine), etc.

[0023] This application employs phospholipids, cholesterol, and fluorophenylboronic acid grafts (such as DSPE-PEG-FPBA), and optionally immunomodulators or other drugs or factors, preferably prepared via reverse evaporation to produce glucose-responsive liposomes or their pharmaceutical formulations. More specifically, lecithin, cholesterol, and DSPE-PEG2K-FPBA (commercially available) are dissolved in chloroform in a certain proportion, and then the resulting solution is mixed with chloroethane containing octadecylamine (or optionally the specific immunomodulator APY29, commercially available). The resulting solution is further sonicated to obtain a homogeneous emulsion. The organic solvent can be removed using a rotary evaporator to obtain a colloidal product; finally, hydration is performed to prepare a liposome emulsion; the liposome emulsion is obtained by sonication and filtration using 450nm and 220nm polycarbonate membranes to obtain the corresponding glucose-responsive liposome material. The liposome structure requires relatively uniform particle size, and is prepared as a single-compartment liposome; multi-compartment liposomes will lead to decreased liposome responsiveness and affect the therapeutic effect.

[0024] DSPE-PEG2K-FPBA can also be replaced by DPPE-PEG-FPBA or DOPE-PEG-FPBA; the molecular weight of the PEG segment in the fluorophenylboronic acid graft is preferably 1000-3000, more preferably 2000. The mass ratio of the phospholipids, cholesterol, and fluorophenylboronic acid graft is preferably 40:10:1-4; blank liposome materials can be prepared from lecithin, cholesterol, octadecylamine, and DSPE-PEG2K-FPBA. If immunomodulators such as APY29 or other factors are added, a glucose-responsive liposome formulation is formed.

[0025] In the embodiments of this application, the sugar-responsive liposome formulation is loaded with the immunomodulator APY29 within its membrane, and its overall external appearance is that of nanospheres with FPBA grafted structures modified on its surface; APY29 is a highly efficient and selective IRE1α small molecule regulator with the following structural formula.

[0026]

[0027] In the embodiments of this application, it is generally required that the drug encapsulation efficiency of the liposomes reach 80% or higher. The release rate of the immunomodulator in the glucose-responsive liposome formulation is positively correlated with the glucose concentration; at high glucose concentrations, the drug release can reach 80% within 72 hours, while at low glucose concentrations, it is only 20-30%.

[0028] Electrospinning, due to its similarity to the natural extracellular matrix (ECM), is widely used to replicate the physiological microenvironment that guides cell fate and regulates tissue regeneration. Because functional electrospinning can autonomously respond to external stimuli and actively fine-tune the delivery of therapeutic compounds, it is considered a promising candidate for periosteal regeneration. Regulating the local immune microenvironment and in situ osteoblast differentiation of mesenchymal stem cells is crucial for diabetic bone defects. This application considers loading liposomes with a specific immunomodulator (APY29) and binding them to type I collagen (COLI) for self-assembly. To achieve this, liposome surface modification with glucose-responsive groups, along with collagen self-assembly and electrospinning, is employed to progressively construct a biomimetic microenvironment-responsive fiber composite system.

[0029] This application provides an oriented electrospun membrane for periosteal regeneration and bone angiogenesis in a diabetic environment, characterized by time-dependent immunomodulation and bone vascularization. This novel fibrous membrane comprises an oriented nanofiber scaffold and a self-assembled material composed of type I collagen and the aforementioned glucose-responsive liposome formulation. The liposome-modified FPBA groups on the surface of this spun membrane are expected to respond to a high glucose environment, leading to changes in the hydrophilicity of the liposome membrane, increased outer membrane swelling, and disruption of the lipid bilayer, resulting in the release of encapsulated APY29. Subsequently, the released APY29 polarizes macrophages towards the M2 phenotype and induces the secretion of osteogenic and angiogenesis-related factors. The ordered electrospun scaffold described in this application will possess multiple functions, such as glucose response, bone immunomodulation, bone induction, and angiogenesis.

[0030] This application uses oriented nanofiber membranes as fiber scaffold materials. Nanofibers of different orientations can be prepared through electrospinning, and the resulting oriented nanofiber membranes are collected. Choosing between ordered and disordered spinning is a challenge when considering the spun membrane as a platform and carrier for cell growth. Under normal conditions, spun membranes are typically spun in a disordered manner. However, disordered spinning has slightly weaker mechanical properties as a cell carrier, offering less intervention in cell growth morphology, and cells are less likely to grow on the spun membrane surface. Therefore, this application chooses ordered spinning, which offers better mechanical properties. Furthermore, ordered spun membranes can influence cell morphology, such as guiding macrophages towards the elongated spindle-shaped M1 morphology, which is more conducive to cell growth and macrophage phenotypic conversion.

[0031] Specifically, in this embodiment of the invention, spinning polymers such as PLA are dissolved in dichloromethane (DCM) and N,N-dimethylformamide (DMF); conventional electrospinning equipment is used, such as inserting the formed electrospinning solution into a syringe 10 cm long and 0.9 mm in diameter, to prepare nanofiber scaffold membrane materials with different orientations. Preferably, the feed pump speed for electrospinning is 60-80 μL·min. -1 At 15-20kV, the distance between the needle tip and the parallel electrode receiver is 10-20cm, which can collect parallel-oriented nanofiber membrane scaffolds between the electrode rods.

[0032] The polymer used to prepare the electrospun membrane is polylactic acid (PLA-COOH), a special type of polymer material with carboxyl groups. PLA-COOH was chosen to enhance the interaction between the spun membrane and collagen. Ordinary PLA lacks electron-withdrawing groups such as O and N on its surface, while PLA-COOH has clearly defined carboxyl groups. Its O groups have strong electron-attracting properties and can form hydrogen bonds with the H groups on the surface of type I collagen, thus strengthening the interaction between the two. The oriented nanofiber scaffold described in this invention is made of one or more of polylactic acid (PLA), polycaprolactone, and caprolactone / lactide copolymers, preferably PLA. Polylactic acid, also known as polylactide, is a polyester polymerized from lactic acid and is a non-toxic, non-irritating synthetic polymer. Polycaprolactone is a polymer formed by ring-opening polymerization of caprolactone monomers and has good biocompatibility. For example, the Mw of PLA can be 109–150 kDa; the average fiber diameter of the prepared oriented nanofiber scaffold is preferably 0.8–1.3 μm. In this scheme, the diameter of the spun membrane fiber is about 1 μm, which is relatively coarse compared with general fiber membranes. The purpose is to improve the mechanical properties of the spun membrane, so that it can provide better mechanical support when implanted into animal models later; the thickness of the spun membrane should be appropriate, as both too thick and too thin membranes will reduce the therapeutic effect.

[0033] This invention relates to the construction of a functional membrane: a sugar-responsive liposome formulation and a collagen solution are mixed and then placed on the oriented nanofiber membrane, resulting in the oriented electrospun membrane through self-assembly. This invention primarily utilizes a self-assembled hydrogel to load the liposome formulation onto the surface of the electrospun membrane. Compared to high-voltage electrospraying and emulsion preparation methods that damage the liposome structure, the process conditions of this invention are relatively simple, and the structure and stability of the liposomes are not damaged during preparation.

[0034] Before functionalizing the membrane scaffold with COLI and the prepared liposome formulation, this invention also includes sterilizing the oriented nanofiber membrane, such as with 75% ethanol, followed by rinsing with water (usually deionized water) to remove any residual ethanol. In this embodiment, lyophilized type I collagen (Collagen I) can be dissolved in an aqueous acetic acid solution and stored at 4°C until further use is required. In an ice bath, the diluted type I collagen solution is diluted with PBS (10×) at a ratio of 6:1, and the pH of the diluted solution is adjusted to 7.0 with an aqueous NaOH (0.1M) solution. Then, in this embodiment, the prepared liposome formulation is added to the neutralized collagen solution, stirred thoroughly, and placed on an electrospinning membrane. Finally, in this embodiment, the sample can be placed in an incubator at 35-38°C for at least 30 minutes to allow self-assembly, followed by washing to obtain the final product. Type I collagen is mainly distributed in tissues such as skin and tendons, and is also the most abundant protein in aquatic product processing waste (skin, bone, and scales), accounting for about 80% to 90% of the total collagen content. It has the most widespread medical applications. Type I collagen is rod-shaped, composed of three peptide chains, and the amino groups in its molecules can bind to the hydroxyl groups in liposome molecules. The Sigma rat type I collagen used in this embodiment of the invention can be 300 kDa, but is not limited to this; for example, it can be 200 kDa to 350 kDa. In this embodiment of the invention, the above-mentioned liposome preparation is mixed with type I collagen and then self-assembled. The resulting hydrogel state satisfies the rheological requirements for modifying liposomes onto the surface of an electrospun membrane to a certain extent. If liquid collagen alone is implanted, it will disperse throughout the body and cannot act on the surface of bone defects for a long time, affecting the bone repair effect. The oriented electrospun membrane described in this embodiment of the invention has a certain degree of hydrophilicity, and the composite self-assembled material is uniformly distributed on the membrane surface.

[0035] In some embodiments of the present invention, the mass-to-volume ratio of the liposomes to type I collagen can be 15.6:100 (15.6 μg of liposomes dissolved in 100 μl of type I collagen solution), which can effectively self-assemble; the ratio loaded onto the oriented fiber membrane is 15.6:100 (w / v), which can be in the range of 15 to 16:100 (w / v). The added liposomes will slightly weaken the self-assembly of type I collagen, but the overall impact is not significant.

[0036] pass Figure 2The study of this system in treating periosteal defects in diabetic rats revealed that the PCLA isooriented electrospun membrane of this application, by blocking the IREα / NOD-like / NFκB signaling pathway, remodeled the pathological diabetic microenvironment into a regenerative microenvironment, while simultaneously reprogramming the macrophage transition from the M1 to the M2 phenotype, enhancing osteogenic differentiation and angiogenesis. In summary, the findings indicate that PCLA modulates the immune microenvironment and enhances bone integration in periosteal defects in diabetic patients. Furthermore, this study provides an effective strategy for designing functionalized biomaterials for bone regeneration therapy in diabetic patients. Attached Figure Description

[0037] Figure 1 This is a schematic diagram of the preparation process of sugar-responsive liposomes and oriented electrospun membranes in some embodiments of the present invention;

[0038] Figure 2 A schematic diagram illustrating the functional characterization of the oriented electrospun film prepared in some embodiments of the present invention;

[0039] Figure 3 SEM and fiber diameter characterization of PLA and PC composite materials in embodiments of the present invention;

[0040] Figure 4 TEM characterization of liposome materials in embodiments of the present invention;

[0041] Figure 5 PDI characterization of liposome materials in the embodiments of the present invention;

[0042] Figure 6 SEM characterization of the PCL group composite material in the embodiments of the present invention;

[0043] Figure 7 XPS characterization of the composite materials in each group of embodiments of the present invention;

[0044] Figure 8 AFM characterization of the composite materials in each group of embodiments of the present invention;

[0045] Figure 9 The adhesion ability, elastic modulus, water contact angle and drug release rate of each group of composite materials in the embodiments of the present invention are characterized.

[0046] Figure 10 Cell compatibility of each experimental group in the embodiments of the present invention;

[0047] Figure 11 This invention relates to the in vitro regulation of macrophage polarization phenotypes in various experimental groups according to embodiments of the invention.

[0048] Figure 12 The experimental groups in the embodiments of the present invention exhibit enhanced immune regulation to promote in vitro osteogenic and angiogenic differentiation.

[0049] Figure 13 This invention relates to the in vivo regulation of bone remodeling by PCLA-oriented electrospun membranes in an embodiment of the invention. Detailed Implementation

[0050] The technical content disclosed in this invention will be clearly and completely described below with reference to the embodiments of this invention. Obviously, the described embodiments are only some embodiments of this invention, and not all embodiments. Based on the embodiments of this invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of this invention.

[0051] Based on sugar-responsive liposomes and electrospinning, this invention constructs a composite material system that dynamically regulates the immune microenvironment and promotes sequential osteogenic and angiogenesis in a diabetic environment, and performs functional characterization and verification.

[0052] Example

[0053] I. Materials and Methods

[0054] 1. Materials

[0055] 1.1 Main Drugs and Reagents: PLA (Mw = 109–150 kDa, IV = 4.0–5.0) was obtained from Jinan Dagang (Daigang Biotechnology Co., Ltd.). Rat tail type I collagen (300 kDa) was purchased from Sigma Aldrich (USA). Dulbecco's modified culture medium (DMEM), fetal bovine serum (FBS), trypsin, and penicillin / streptomycin were purchased from Gibco (USA).

[0056] 1.2 Main instruments: rotary evaporator (Qiuzuo Technology, China), high voltage electrode (Huizhi Electrospinning, China), propulsion pump (Huizhi Electrospinning, China), Micro-CT (SkyScan 1176, Belgium), paraffin sectioner (Leica 2135, Germany), slide burner (Leica 1120, Germany), paraffin embedding machine (BMJ-II, Changzhou, China), Axiovert 40C optical microscope (Zeiss, Germany), a set of surgical instruments, etc.

[0057] 1.3 Experimental Animals: Forty healthy male SD rats, weighing 300±20g, 12 weeks old, clean-grade, were provided by the Animal Experiment Center of Soochow University. Feeding conditions were as follows: room temperature 18–20℃, humidity 50–60%, good ventilation, and free access to food and water.

[0058] 2. Experimental Methods

[0059] 2.1 Preparation of Oriented Nanofiber Scaffolds: PLA (0.5 g) was dissolved in dichloromethane (4.0 g, DCM, Sinopharm Reagent Co., Ltd., Beijing, China) and N,N,DMF (2.0 g, Shanghai Lingfeng, Shanghai, China). The electrospinning solution was inserted into a 10 cm long, 0.9 mm diameter syringe to prepare fiber scaffolds with different orientations. The electrospinning pump speed was 70 μL / min. -1 At 18kV, the distance between the needle tip and the parallel electrode receiver is 15cm. Parallel-oriented fiber scaffolds are collected between the electrode rods.

[0060] 2.2 Preparation of Glucose-Responsive Liposomes: Glucose-responsive liposomes were prepared by reverse evaporation. More specifically, lecithin (160 mg, Shanghai Yuanye, China), cholesterol (40 mg, Arcos, Belgium), and DSPE-PEG2K-FPBA (4 mg, Shanxi Ruixi, China) were dissolved in chloroform (5 mL, Shanghai Lingfeng, Shanghai, China). The resulting solution was then mixed with 1 mL of chloroethane containing octadecylamine (5 mg, Shanghai Aladdin Chemical Co., Ltd., China) and APY29 (4 mg, Shanghai MCE, China). The resulting solution was further sonicated to obtain a homogeneous emulsion. The organic solvent was removed using a rotary evaporator to obtain a colloidal product, which was finally hydrated to prepare the liposome emulsion. The glucose-responsive liposome formulation was obtained by sonication and filtration using 450 nm and 220 nm polycarbonate membranes (Millex-GP, Ireland). Blank liposomes were prepared from lecithin, cholesterol, octadecylamine, and DSPE-PEG2K-FPBA (40:10:5:4, w / w / w / w). All liposomes were stored after lyophilization.

[0061] 2.3 Construction of Functional Membranes: Before functionalizing pure PLA membranes with COLI and prepared liposomes, the membranes were first sterilized with 75% ethanol for 30 minutes, and then rinsed three times with deionized water to remove any residual ethanol. Lyophilized type I collagen was dissolved in an aqueous acetic acid solution (collagen solution concentration 0.1M, 3 mg / ml). -1 The liposomes were then stored at 4°C until further use was required. The diluted type I collagen solution was diluted with PBS (10×) at a ratio of 6:1 in an ice bath, and the pH of the diluted solution was adjusted to 7.0 with NaOH (0.1M) aqueous solution. The prepared liposomes (15.6 μg) were then added to the neutralized collagen solution (100 μL), stirred thoroughly, and placed on an oriented electrospun membrane. Finally, the sample was placed in an incubator at 37°C for 30 minutes to allow self-assembly. The self-assembled sample was washed three times with deionized water to obtain the composite PCLA membrane, PCL membrane, and PC membrane, which were immediately used for further material characterization or cell experiments.

[0062] It should be noted that pure PLA membranes are pure polylactic acid spun membranes; PC is short for PLA / Collagen I, which is simply collagen assembled on the surface of a polylactic acid spun membrane; PCL is PLA / Collagen I / Liposome, which is PC with the addition of blank liposomes; these three groups serve as the control group, while PCLA is PCL with APY29 loaded into the liposomes, designated as the experimental group. Furthermore, all the above preparation processes are simple and straightforward.

[0063] 2.4 Material Characterization and Results:

[0064] SEM was performed using a Hitachi S-4800 scanning electron microscope (Japan). The average fiber diameter of 200 random fibers was measured using ImageJ. The orientation of the fiber scaffold was determined using the orientation plug of ImageJ, while the structure of the samples was imaged using a confocal microscope (Axio Imager M1, Zeiss, Germany). FTIR spectra were obtained on a Frontier™ Fourier transform infrared spectrometer (PerkinElmer, USA). Rheological tests and water contact angle measurements were performed using a HAAKE RheoStress 6000 instrument (Thermal Sciences, USA) and a contact angle meter (Data Physics, Inc.). Mechanical properties and nanofiber surface elements were investigated using a general kinetic testing system (Shanghai Hengyi, China) and an XPS system (250Xi, Scientific Escalab, USA), respectively. The topological morphology of the fiber surface was observed using an AFM (Dimension ICON, Bruker, USA), while the surface morphology of the liposomes was observed using a TEM (HT7700, Hitachi, Japan). Particle size, PDI, and zeta potential of each mixture were measured using a dynamic light scattering particle size analyzer (Nano-ZS 90 Zetasizer, Malvern, UK). To measure the release of APY29 from liposomes at different glucose concentrations (25, 5.6, and 0 mM), liposomes were immersed in 50 mL centrifuge tubes containing the corresponding glucose solution (10 mL) for 3, 6, 9, 12, 15, 18, 21, and 24 hours. The extent of APY29 release was determined using HPLC (Agilent system with Kromasil 100-5C18 column), and the corresponding cumulative release curves were plotted.

[0065] Ordered spun membranes were constructed using a poly(DL-lactide) COOH solution on a parallel electrode receiving device via electrospinning. More specifically, liposomes were mixed with DSPE-PEG2K-FPBA and APY29 to generate glucose-responsive drug-carrying nanospheres, which were then self-assembled on aligned spun nanofibers after mixing with COLI. The composite material exhibited uniform distribution, robust plasticity and mechanical properties, and reactivity with glucose.

[0066] Scanning electron microscopy (SEM) imaging confirmed the regular, oriented, and smooth fiber distribution in the PLA group collected using a parallel electrode receiver. Figure 3 b1). After PLA nanofiber films are assembled with COLI, the collagen in the films is tightly bound together by electrospinning and uniformly deposited on the spun films to create a micro / nanofiber layered structure. Figure 3 c1). Quantitative analysis showed that the average spinning diameters of PLA and PC oriented electrospun films were 1.04±0.23μm and 1.09±0.20μm, respectively, with a distribution pattern ( Figure 3 (b2 and c2).

[0067] Liposomes (blank liposomes) were dissolved in phosphate-buffered saline (PBS), low-glucose (LG) medium, and high-glucose (HG) medium for 2 hours to verify their glucose reactivity. For the PBS group, transmission electron microscopy (TEM) imaging showed a typical phospholipid bilayer structure in most liposomes. However, in the LG and HG groups, the bilayer structure of some liposomes was disrupted, and their diameter increased; this trend was more pronounced in the HG group. Figure 4 To verify the changes in the core-shell structure of liposomes under different glucose concentrations, dynamic light scattering was used to assess the size dispersibility of liposome microsol particles. The polydispersity index (PDI) is used to describe the degree of heterogeneity in particle size distribution; a relatively small PDI value indicates relatively uniform particle dispersion. Experiments showed that increasing the glucose concentration in the solution increased the liposome particle size, while the surface charge and PDI decreased. Figure 5 (e.g.) More specifically, the mean diameter and PDI of the microsol particles in the HG group were determined to be 544.42±24.90 nm and 0.64±0.071, respectively; however, the lower PDI was observed, indicating uniform particle size distribution. The mean diameters of the microsol particles in the LG and PBS groups were 341.52±19.95 nm and 266.42±21.89 nm, respectively, with corresponding PDIs of 0.84±0.065 and 0.81±0.038, respectively. However, the particle distribution was not as uniform as in the HG group. The data suggest that in the HG group, liposomes without structural bilayer rupture were more stable and more uniform in size. The reduction in surface charge in the HG group may be due to changes in the FPBA structure and the negative charge generated by FPBA binding to glucose in high glucose solutions. Since the immunomodulatory capacity of electrospun fibers depends primarily on their thin-film surface structure, TEM was used to investigate the assembly and structure of the thin film on the spinning surface. Compared with the PC group, the liposomes in the PCL group were more evenly distributed between the spindles, proving that the liposome transplantation was successful and that the liposomes and collagen were tightly bound together. Figure 6 ).

[0068] X-ray photoelectron spectroscopy (XPS) was used to determine changes in the surface chemistry of the fibrous scaffold and to validate the construction of type I collagen and liposomes. Results showed that group PLA elements were predominantly C and O, while no signal was observed in group B elements. Furthermore, as... Figure 7 As shown in figure a, the C1s signal corresponds to polylactic acid. For the PC group, the presence of CP, CN, NC=O, and other components was confirmed in the C1s spectrum, thus confirming the successful introduction of COLI. Figure 7 b). For the PCL group, C, O, N, and H were present, and signals were also observed in the B1s spectrum. These results indicate that the introduction of liposomes / FPBA was successful, and the presence of signals corresponding to CB bonds in the C1s spectrum further confirms this. Figure 7 c). Compared to the PCL group, the PCLA group contains more NC=N bonds, thus proving the existence of APY29. Figure 7 d).

[0069] To further investigate the binding modes between the fibrous scaffold, collagen, and liposomes, Fourier transform infrared (FTIR) spectroscopy was used to identify the chemical bonds in four electrospun fibers (PLA, PC, PCL, and PCLA). At 1751 cm⁻¹ -1 The characteristic absorption peak of PLA observed at [location] corresponds to the typical C=O tensile vibration of PLA. In contrast to the spectrum observed in the electrospun sample, the composite product after COLI binding [spectrum] at 3333 cm⁻¹ -1 A weak, broad peak appears at 3287 cm⁻¹, mainly due to hydrogen bonds between electrospun fibers and collagen. After liposome binding, the peak is at 3287 cm⁻¹. -1 The shift in the –OH absorption peak at 2944 cm⁻¹ confirms that the addition of drug molecules altered the hydrogen bonding forces present in the polymerization system. Due to the weak hydrogen bond interactions between the drug-related groups and the liposomes / electrospun collagen, the CH absorption peak was observed at 2944 cm⁻¹. -1 The significant changes at the site confirm this. Therefore, the disappearance of several characteristic peaks and the appearance of new characteristic peaks confirm that the electrospinning process with the collagen / drug-loaded liposome complex was successful.

[0070] It should be noted that the formation of this complex depends primarily on hydrogen bonding, particularly the strong hydrogen bonds between the collagen HN groups and the OC portion of the electrospun fibers. Hierarchical micro / nanofiber structures fabricated from collagen and electrospun fibers have the potential to guide the behavior of bone marrow mesenchymal stem cells (BMSCs), including their adhesion, proliferation, and further differentiation, which are essential for inducing osteogenic formation in vivo. To further investigate this, atomic force microscopy (AFM) was used to examine variations in the surface roughness values ​​(Ra, roughness) of the four groups of materials. Figure 8 ).

[0071] The obtained AFM phase diagram showed the presence of ring-shaped protruding liposomes on the PCLA membrane surface, indicating that the liposomes are stably bonded to the fiber surface. The adhesion strength of the four materials was measured, and it was found that the adhesion strength of PC, PCL, and PCLA membranes was greater than that of pure PLA membrane (24.66±4.34, 43.82±4.33, 49.52±3.53, and 52.42±3.74 nN, respectively). Figure 9 g). This is likely due to the enhanced tissue adhesion of the COLI hydrogel compared to PLA electrospinning. Furthermore, the enhanced adhesion observed in the presence of liposomes can be attributed to their H-bond interaction with the ColI hydrogel. As an important foundation of bone tissue engineering, scaffolds not only provide a growth platform for cells but also guide the bone remodeling process. Therefore, the elastic modulus of the prepared specimens was evaluated. More specifically, PC (36.64 ± 1.26 N / mm²) -2 PCL (39.49±1.88N mm) -2 ) and PCLA (40.31±0.81N mm) -2 The elastic modulus of is higher than that of PLA (23.41 ± 0.81 N / mm). -2 ()( Figure 9 These results were attributed to the self-assembly of COLI and the presence of hydrogen bonds between collagen and the electrospinning surface, as well as between liposomes and collagen. Subsequently, the water contact angles of PLA, PC, PCL, and PCLA fibers were determined to be 122.30±4.49, 59.19±7.27, 42.65±4.62, and 38.59±6.56°, respectively. Figure 9 i). These values ​​clearly show that the water contact angle decreased by approximately 60° after collagen assembly, indicating that COLI nanofibers possess significant hydrophilicity. Therefore, the hydrophilicity of PCL and PCLA membranes is slightly higher than that of PC membranes, and the water contact angle of PCL and PCLA fibers is significantly reduced due to the hydrophilicity of phospholipids on the liposome surface extending into the aqueous phase to enhance hydrophilicity.

[0072] The bone microenvironment in diabetes leads to the formation of a hyperglycemic environment in localized areas. Based on this pathological feature, an in vitro simulation was used to detect the release of reactive drugs under a hyperglycemic environment. More specifically, this was achieved by immersing electrospun membranes and drug-loaded liposomes in environments containing different glucose concentrations (high glucose: 25.0 mmol / L). -1 Low glucose: 5.6 mmol / L -1 In the culture medium of PBS, the drug (APY29) release rate of three groups of liposomes (PBS, LG, and HG) at different time points (2, 4, 6, 12, 24, 48, and 72 hours) was determined. Figure 9(j) In all three groups, the degree of drug release from the liposomes gradually increased over time. However, in the high glucose group, the release rate of APY29 reached 86.19 ± 0.68% at 72 h, significantly higher than that in the LG group (65.09 ± 1.71%) and the PBS group (12.18 ± 0.38%). Therefore, the rapid response of these reactive fibrillary scaffolds to a high glucose environment was validated in vitro, providing a basis for further research.

[0073] 2.5 Preparation of cell cultures: RAW264.7 cells were cultured in DMEM (Hyclon) at 37°C, and BMSCs were cultured in α-MEM containing 5% CO2, both containing 10% FBS (Gibco) and 1% penicillin / streptomycin. Before cell culture, the hybrids were sterilized overnight under UV light with ethanol, and then washed with sterilized PBS.

[0074] 2.6 Cell Viability and Proliferation: After 3 days of culture, BMSCs and RAW264.7 cells were stained using a live / dead cell staining kit (Invitrogen, USA) to assess their viability on different nanofiber membranes. The stained cells were observed under a fluorescence microscope (Axio Imager M1, Zeiss, Germany) and semi-quantitative fluorescence analysis was performed using ImageJ. A cell counting kit-8 (NCMBio, Suzhou, China) was used to study the proliferation rate of BMSCs on the cell membrane at 3 and 7 days post-transplantation. More specifically, BMSCs (5 × 10⁶ cells / year) were counted on different nanofiber membranes. 3 Cells / well were implanted into 96-well plates (100 μg per well). On days 3 and 7, absorbance of each plate was measured using a microplate reader at an optical density of 450 nm (Biotek, USA).

[0075] 2.7 Cell adhesion: BMSCs (1×10⁻⁶) were placed in the cell membrane. 4Cells (1 cell / well) were seeded on cell crawlers containing hybrid material extract. After one day of co-culturing in 24-well dishes, cells were fixed on ice with 4% paraformaldehyde for 30 minutes and perforated with a solution containing 0.1% Triton X-100 for 10 minutes (Sigma Aldrich, USA). To avoid nonspecific staining, cells were blocked overnight at 4°C using bovine serum albumin. Cells in the medium were then fixed with 4% paraformaldehyde and incubated overnight at 4°C with a protein antibody (ab130007, Abcam). Subsequently, cells were washed with PBS containing 0.1% Tween to remove any unconjugated primary antibody and then incubated with a fluorescent secondary antibody (ab150115, Abcam) for 1 hour. FITC phalloidin was then added to stain F-actin, and 4′,6′-diamidinyl-2-phenylindole (DAPI) was added to stain the nuclei. Fluorescence images were obtained using a fluorescence microscope under laser excitation (Axio Imager M1, Zeiss, Germany).

[0076] 2.8 Cell morphology: BMSCs (2×10⁻⁶) were used. 4 Cells were cultured (1 cell / well) for 3 days and fixed with 4% paraformaldehyde on ice for 1 hour. Subsequently, the cells were washed for 15 minutes with different concentrations (30, 50, 70, 80, 90, 95, 100, and 100%) of ethanol. After drying in a CO2 critical point dryer for approximately 2 hours, the sample surface was gold-plated for 45 seconds, rinsed three times with PBS, and fixed with paraformaldehyde for 30 minutes to obtain SEM images.

[0077] 2.9 In vitro osteogenicity: The osteogenic capacity of the prepared materials was assessed using an alkaline phosphatase assay kit (Beyotime Biotechnology, Shanghai, China). More specifically, BMSCs (1 × 10⁻⁶) extracted from different populations were used to assess osteogenic capacity. 4 Cells were seeded at 100 cells / well in 24-well plates. After 7 days, cells were fixed with 4% paraformaldehyde. Subsequently, alkaline phosphatase staining solution (300 μL / well) was added to each well in the dark and the cells were incubated for 30 minutes. Stained (positive) cells were visible under an optical microscope. After 2 days of culture, cells were fixed in 4% paraformaldehyde solution for 30 minutes. Subsequently, cells were cleaned several times with PBS to remove excess dye, and calcium nodules were observed under an optical microscope. To quantify the ARS staining results, 5% perchloric acid was added to each well, and uptake was measured at 490 nm.

[0078] 2.10 Immunofluorescence: Initially, BMSCs were washed three times with PBS and incubated in cold paraformaldehyde for 15 minutes. Then, BMSCs were blocked with QuickBlock™ IF blocking solution (Beyotime Biotech) and incubated at 4°C for 1 hour, followed by overnight primary antibody incubation at 4°C. After two subsequent PBS washes, BMSCs were incubated with IgG H&L antibodies (Alexa Fluor 647; Abcam, ab150079; Alexa Fluor 488; Abcam, ab150165) for 1 hour. Finally, BMSCs were stained with DAPI, and intracellular protein expression was observed using confocal fluorescence microscopy.

[0079] 2.11 In vitro angiogenesis: The angiogenesis capacity of different material groups was observed using growth factor reducing agent substrate (100 μg / well, Corning, USA). Then, HUVECs (3.5 × 10⁻⁶) were... 4 (200 cells / well) were seeded into each well of the mixture. After incubation at 37°C in an environment containing 5% CO2, each plate was observed using an optical microscope at 0, 3, and 6 hours. Migration ability was verified using Transwell plates (Corning). Specifically, PLA, PC, PCL, and PCLA extracts were placed in the lower chamber while HUVEC suspension (200 μL, 2.5 × 10⁻⁶ cells / well) was added. 5 cells / ml -1 Add the membrane to the upper chamber and incubate at 37°C in an environment containing 5% CO2. After 16 hours of incubation, remove the incubator, carefully remove the membrane with a cotton swab, and fix with 4% paraformaldehyde for 20 minutes. Then stain the cells with 0.1% crystal violet solution (Solarbio, Beijing, China) and observe them under a light microscope. Assess wound healing to evaluate angiogenesis, and use 4×10⁻⁶ cells. 5 Cells / well were seeded in 6-well plates and incubated at 37°C in an atmosphere containing 5% CO2. When the cell flow rate reached 90% fluency, a scribbling motion was made on the cell layer using the tip of a 200 μL pipette. All images were captured using an inverted microscope at 0, 12, and 24 hours.

[0080] 2.12 Identification of macrophage phenotype:

[0081] Polarized RAW264.7 cells exhibited altered gene expression levels under the influence of reactive fibrillary membranes. Cells were then incubated with the major antibodies iNOS (M1-labeled) and Arg-1 (M2-labeled) containing F-actin and stored overnight at 4°C. Solutions were prepared using IgG H&L (Alexa Fluor 647, red; Akam; Alexa Fluor 488, green; Abcam) and DAPI. All images were captured using fluorescence microscopy. On day 7 of co-culture, M1 and M2 macrophages were treated with iNOS (Abcam, ab49999, 1:100) and Arg-1 (Abcam, ab239731, 1:100) and then incubated with goat anti-rabbit (Abcam, ab155079, 1:200) and goat anti-mouse (Abcam, ab150113, 1:400). Semi-quantitative analysis was then performed using ImageJ. Cell suspensions from different groups were centrifuged at 300g for 10 minutes, antibodies were added for 30 minutes, and then further incubated at 4°C. For this purpose, the following mouse conjugate antibodies were used: mouse anti-CD11b-APC (562102, 1:20; BDPharmingen), mouse anti-CD86-FITC (561961, 1:20; BD Pharmingen), and mouse anti-CD206-PE (sc-58986, 1:50; Santa Cruz Biotechnology). Cells were then analyzed using flow cytometry (Merck Millipore, USA), and the results were analyzed using FlowJo 7.6. For this purpose, cells were initially gated with CD11b to ensure that only RAW264.7 cells were selected, and then a combination of specific markers was used to identify M1 (CD86) and M2 (CD206) macrophages. Three samples (n=6) were randomly selected from each group.

[0082] 2.13 RT-PCR: Total RNA was isolated from BMSCs according to standard protocols. mRNA concentration and purity were assessed using a NanoDrop-2000 (Thermo Fisher Scientific, Waltham, MA, USA). The expression was calculated using the 2-ΔΔCq method.

[0083] 2.14 Preparation of conditioned media: A combination of conditioned media was collected to induce osteogenic and angiogenesis. For this purpose, RAW264.7 cells (4 × 10⁻⁶) were conditioned media prepared. 5 Cells were cultured in 6-well plates in an atmosphere containing 5% CO2. After culture, cells were treated with LPS (100 ng / mL). -1 Each culture medium was treated for 12 hours, and then the supernatant from different groups was collected and filtered to remove cell debris in a sterile environment.

[0084] 2.15 Animal Model: Female Sprague-Dawley rats (average weight: 200-250 g) purchased from the Experimental Animal Center of Soochow University (ethics approval number: 20220925A01). The rats were administered STZ (35 mg / kg) via intraperitoneal injection. -1 Blood was extracted and stored weekly from the tail vein for glucose level analysis; values ​​>16.7 mm were considered a successful diabetes model. Rats were then anesthetized intraperitoneally with 2% sodium pentobarbital. After thorough shaving and disinfection, a longitudinal incision was made in the center of the surgical area, and the soft tissue was carefully dissected to expose the skull. The periosteum was removed, and two bilateral defects, each 5 mm in diameter, were carefully created on the skull using a toothed trephine to simulate poor skeletal condition and periosteal defects. The defect areas were then covered with a thin film. Penicillin was injected once daily for 3 days.

[0085] 2.16 Micro-CT Assessment: SD rats were euthanized at 4 and 8 weeks post-surgery, and skull specimens were collected and fixed in 10% formalin for further identification. Micro-CT (SkyScan 1176, SkyScan, Belgium) was initially used to assess regenerative conditions in defective areas using settings such as 65kV, 385mA, and a 1mm Al filter. The skull was reconstructed in 3D using Mimics software. To calculate BV / TV, BMD, Tb.N, and Tb.Sp, a cylindrical space representing the region of interest was specified to assess bone and tissue volume. These values ​​were obtained using CT Analyzer software (SkyScan, Belgium). 3D reconstructed images were performed using Mimics (version 21.0).

[0086] 2.17 Histological Analysis: At 2, 4, and 8 weeks post-surgery, each skull fragment was removed and fixed / decalcified with 10% formic acid at room temperature for one week, followed by gradient alcohol dehydration and paraffin blockade. Embedded specimens were sectioned into 6 μm thick histological sections centered on the defect area, and morphological changes were observed under a light microscope using routine H&E and Masson staining (Carl Zeiss). The levels of iNOS, CD31, Runx2, and periosteal protein markers were also identified by immunohistochemical staining. More specifically, sections were dewaxed and gradient hydrated at 37°C for 30 minutes prior to trypsin treatment. After 30 minutes, diluted horse serum was added to block any nonspecific sites, followed by three PBS cleanses. Subsequently, the major antibody was added and incubated overnight at 4°C. The sections were then cultured for 30 minutes with the appropriate secondary and third antibodies.

[0087] 2.18 Statistical Analysis: Data are presented as standard deviation ± mean. Unless otherwise specified, statistical analysis (Origin 9.1 or GraphPad Prism 7.0 software) assesses differences between groups using one-way or two-way ANOVA with Tukey's multiple comparison test. A p-value < 0.05 is considered statistically significant.

[0088] II. Functional Test Results

[0089] (1) In vitro biocompatibility: The in vitro biocompatibility of PLA, PC, PCL, and PCLA materials was subsequently assessed by seeding mouse macrophages (RAW264.7 cells) and BMSCs onto the surface of the spun membranes. For this purpose, live / dead cell staining was initially performed. Compared to the surface of naked lactic acid spun fibers, the number of dead cells in the PC, PCL, and PCLA groups was significantly reduced ( Figure 10 a and 10b), confirmed by quantitative analysis of live / dead cells (a and 10b) Figure 10 c). To further understand the proliferation of RAW264.7 cells, cell counting kit-8 method was performed after co-culturing cells with four fiber groups for 3 and 7 days. Figure 10 d). The results showed that RAW264.7 cells grown on the surfaces of PC, PCL, and PCLA had good viability, which may be due to the synergistic effect of type I collagen and liposomes in promoting cell proliferation.

[0090] (2) The effect of PCLA-based immune response regulation under simulated DM conditions:

[0091] Bone immune cells are essential for osteogenic and angiogenesis, especially in the early immune setting. To investigate the ability of PCLA to reprogram macrophages in a diabetic inflammatory microenvironment, a high-glucose medium and lipopolysaccharide (LPS) were initially used to simulate the diabetic metabolic inflammatory environment. Subsequently, phenotypic changes in cultured macrophages seeded on PCLA surfaces were examined. Figure 11 a). In the PLA, PC, and PCL groups, macrophages mainly adopted a pancake-like morphology, while in the PCLA group, macrophages were elongated ( Figure 11 b). Furthermore, the fluorescence intensity of M2 polarization-related proteins was significantly increased in the elongated cells on the PCLA surface, indicating that macrophages polarized from a pro-inflammatory M1 state to an anti-inflammatory M2 state. (e.g.) Figure 11As shown in c and 11d, compared with the other three groups, the PCLA group showed a significant increase in M2 macrophages (Arg-1+, green). In contrast, M1 macrophages (iNOS+, green) were dominant in the PLA group. Notably, compared with the PLA group, Arg-1 was slightly upregulated and iNOS was slightly downregulated in both the PC and PCL groups. Flow cytometry was used to further explore the M1 and M2 phenotypic switches at the cellular level. Figure 11 e and 11f). The results showed that the CD11b+ / CD206 ratio of the APY29-loaded scaffold was significantly higher than that of the scaffold without APY29, and the corresponding ratios in the PC, PCL, and PLA groups were also significantly increased after the addition of COLI, being 161% and 211% higher than that in the PLA group, respectively. Similarly, the expression of CD11b+ / CD86 in the PCLA group was significantly lower than that in the PLA, PC, and PCL groups. These significant differences suggest that PCLA can manipulate macrophage behavior and strongly influence the immune environment. Next, we detected a number of inflammatory and anti-inflammatory factors. The results showed that the PLA group had higher expression of pro-inflammatory factors such as interleukin-1β (IL-1β), while the PCLA group had higher expression of the anti-inflammatory factor IL-10. Therefore, PCLA appears to significantly inhibit the secretion of pro-inflammatory cytokines and promote the expression of anti-inflammatory cytokines. In addition, the key roles of osteogenic-related genes in regulating osteogenic and angiogenesis were well elucidated, and the results showed that the expression of osteogenic and angiogenesis-related markers (BMP-2 and VEGF-A) was significantly enhanced in PCLA. Figure 11 g).

[0092] In summary, PCLA downregulates the inflammatory response, upregulates anti-inflammatory factors, activates macrophages to transform into the M2 phenotype, and releases a large amount of osteogenic / angiogenic mediators; therefore, it can be considered an effective and beneficial bone immunomodulatory material.

[0093] (3) Bone immune regulation of electrospun scaffold BMSCs and HUVECs under simulated DM conditions:

[0094] Periosteal modulation involves manipulating immune cells through biomaterials to generate a beneficial bone immune environment, thereby regulating new bone formation. Following an early immune response from macrophages, HUVECs and BMSCs are recruited to the implant surface, and the function of ECs and BMSCs is primarily influenced by the macrophage-modulated immune microenvironment. To investigate the effects of immunomodulation on angiogenesis and osteogenicity, RAW264.7 cells pretreated with PL, PC, PCL, and PCLA were stimulated with LPS and collected in conditioned medium (CM). Figure 12 a). Then, the bone immunomodulatory function of PCLA was assessed by collecting macrophage CMs used to culture BMSCs and HUVECs. ALP staining and ALP activity clearly showed that the PC, PCL, and PCLA groups were significantly higher than the PLA group ( Figure 12 b and 12c). Furthermore, on day 21, ARS staining of calcium-binding proteins in the mineralized matrix showed that the number and size of mineralized nodes in the PCLA group were significantly greater than in other groups (b and 12c). Figure 12 (b and 12d). Osteocalcin (OCN) staining also confirmed that the relative expression of OCN in the PCLA group was significantly higher than that in the PLA, PC, and PCL groups, and osteogenic differentiation in the PCLA group was also significantly enhanced. Figure 12 e). The expression levels of other genes associated with osteogenic formation (Runx2, Osterix, and BMP-2) were also examined. Figure 12 fh), their expression in PCLA was significantly higher than in other groups. These results indicate that PCLA has a greater osteogenic differentiation capacity compared to other groups, which may be related to the immunomodulatory properties of APY29, prompting macrophages to secrete osteogenic growth factor BMP-2. The migration results of PCLA-stimulated HUVECs are as follows: Figure 12 As shown in Figure i, the exposed gaps gradually closed due to the directional migration of cells. Compared with the PLA group, HUVECs co-cultured with macrophages exhibited significantly greater migration ability, especially in the PCLA group. Semi-quantitative analysis showed that the wound closure area in the PCLA group was significantly smaller than that in the other three groups at 12 and 24 hours. Figure 12 l), the wound healed completely after 24 hours. Figure 12 Optical images of the capillary network in group j show no evidence of capillary network formation in the PLA group, while the formation of capillary structures (i.e., tubes, nodes, and branches) in the PCLA group was significantly increased compared to other specimens at all predefined time points. Figure 12 m and 12n). Furthermore, analysis of HUVEC migration using crystal violet staining revealed that more cells in the PCLA group were switched to the other side of the Transwell membrane; in fact, very few metastatic cells were observed in other groups. Figure 12 k). Subsequently, VEGF expression was measured after 72 hours of culture. Figure 12 (o). Transcriptional expression of VEGF-A was found to be significantly higher in the PCLA group than in all other groups, which may be attributed to the contribution of APY29 to the regulation of the immune microenvironment, and therefore to VEGF-A secretion by macrophages. Overall, these results suggest that a favorable bone microenvironment under the influence of PCLA leads to robust osteogenic and angiogenic biological activity.

[0095] (4) In vivo performance evaluation: To determine whether PCLA promotes bone fusion in diabetic rats, different material groups were implanted into the surface of skull defects according to the above grouping arrangement. New bone formation in the skull defects was evaluated at 8 and 12 weeks post-implantation. After obtaining the rat skulls, three-dimensional (3D) reconstruction of micro-CT images and histological analysis were performed. More specifically, the reconstructed 3D micro-CT images showed abundant new bone formation in the PCLA group at 6, 8, and 12 weeks, while very little new bone was found in the composite implanted PLA group. Figure 13 a). Quantitative analysis further confirmed this result, revealing that the PCLA group had the highest bone mineral density (BMD), bone volume / tissue volume (BV / TV), and trabecular number (Tb.N), but the lowest trabecular separation (Tb.Sp). Figure 13 (b) Within the same volume of interest, the newly formed trabecular bone exhibited superior structural characteristics. As expected, PCLA showed the strongest bone-forming capacity, likely due to the synergistic effect of APY29 and COLI. In contrast, collagen alone may not provide the optimal immunomodulatory microenvironment for bone regeneration. The newly formed bone was sequentially labeled with calcitonin (green) and alizarin red (red), yielding results similar to those described above. Figure 13 c). More specifically, extensive neomineralization was observed in the PCLA (18.80%), PCL (11.10%), PC (8.22%), and PLA (3.74%) groups. Figure 13 d).

[0096] To further evaluate the effects of various treatments on skull defects in rats, histological staining was performed on harvested samples 12 weeks post-surgery. H&E and Masson staining images of skull defects after different treatments showed that the degree of new bone formation in the PCLA, PCLA, and PC groups was higher than that in the PLA group; the largest bone value was observed in the PCLA group at 12 weeks, indicating a higher degree of osteogenic formation. Figure 13 e). Furthermore, Masson staining showed blue staining in new bone tissue and red staining in cancellous bone in the PCLA group, indicating increased calcification, maturation, and remodeling of the new bone tissue. Figure 13 f). Immunofluorescence showed that OCN and CD31 were highly expressed in cells implanted with PCLA, PCL, and PC, with the PCLA group exhibiting the highest levels of OCN and CD31 expression. Figure 13g). Overall, compared with other groups, the PCLA group promoted osteogenic and angiogenesis in vivo, thus demonstrating its potential for postoperative treatment of skull defects in rats. These results clearly demonstrate that bone immunomodulation and regeneration can occur simultaneously and mutually promote each other. Using arranged spun fibers as carriers combined with type I collagen and PCLA-loaded lipids, wherein the PCLA was modified with a glucose-responsive group, a biomaterial with enhanced bone induction and immunomodulation was obtained. This dual-effect biomaterial not only induces early phenotype conversion from M1 to M2 but also induces direct osteogenic formation, synergistically creating an in vivo microenvironment conducive to bone regeneration. Figure 13 h). To date, glucose-responsive immunomodulatory liposomes have not bound to osteogenic collagen, and their synergistic effect on osteogenic differentiation remains unclear.

[0097] In summary, the pathological diabetic microenvironment, characterized by glucose fluctuations and chronic inflammation, leads to delayed healing of periosteal defects. Therefore, it is necessary to develop novel materials that promote bone integration and are suitable for use in the complex microenvironment of diabetes. This invention preferably develops a novel glucose-responsive PCLA composite material, which modulates the local immune microenvironment and promotes bone integration at the periosteal-implant interface. Studies have shown that PCLA remodels the pathological diabetic microenvironment into a regenerative microenvironment by blocking the IREα / NOD-like / NF-κB signaling pathway, while simultaneously reprogramming macrophages from the M1 to the M2 phenotype, enhancing osteogenic differentiation and angiogenesis. Overall, the findings indicate that PCLA modulates the immune microenvironment and enhances bone integration of periosteal defects in diabetic patients. Furthermore, this study provides an effective strategy for designing functionalized biomaterials for bone regeneration therapy in diabetic patients.

[0098] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. An oriented electrospun membrane for bone regeneration in diabetic settings, characterized in that, The invention includes oriented nanofiber scaffolds and self-assembled materials composed thereof, the self-assembled materials being formed from collagen and sugar-responsive liposome formulations; The collagen is type I collagen; The sugar-responsive liposome formulation comprises: sugar-responsive liposomes and immunomodulators encapsulated thereon; the sugar-responsive liposomes are prepared from phospholipids, cholesterol and fluorophenylboronic acid grafts as raw materials, wherein the fluorophenylboronic acid graft is one or more of DSPE-PEG-FPBA, DPPE-PEG-FPBA and DOPE-PEG-FPBA; The oriented nanofiber scaffold is made of one or more of PLA, PCL, and PCLA; the average fiber diameter of the oriented nanofiber scaffold is 0.8-1.3 μm; the oriented electrospun membrane is hydrophilic and has a water contact angle of 32°-100°. The method for preparing the oriented electrospun film includes the following steps: S1. Nanofibers with different orientations were prepared by electrospinning, and the oriented nanofiber membranes were collected. The sugar-responsive liposome formulation was prepared by reverse evaporation. S2. The sugar-responsive liposome preparation and collagen solution are mixed and placed on the oriented nanofiber membrane, and the oriented electrospun membrane is obtained by self-assembly.

2. The oriented electrospun film according to claim 1, characterized in that, The fluorophenylboronic acid graft in the raw material for preparing the sugar-responsive liposome is DSPE-PEG-FPBA, and the molecular weight of the PEG segment in the fluorophenylboronic acid graft is 1000-3000.

3. The oriented electrospun film according to claim 2, characterized in that, In the raw materials for preparing sugar-responsive liposomes, the mass ratio of phospholipids, cholesterol, and fluorophenylboronic acid grafts is 40:10:1~4.

4. The oriented electrospun film according to claim 1, characterized in that, The immunomodulator in the sugar-responsive liposome formulation is APY29; the release rate of the immunomodulator is positively correlated with the sugar concentration.

5. The oriented electrospun film according to claim 1, characterized in that, The oriented nanofiber scaffold is made of PLA.

6. The oriented electrospun film according to claim 1, characterized in that, In step S2 of the preparation method, the collagen solution is neutral and the solute is type I collagen; the self-assembly temperature is 35-38℃ and the time is more than 30 minutes.

Citation Information

Patent Citations

  • Vesicle compositions

    CN103429226A

  • Liposome drug carrier with mucosal adhesion as well as preparation method and application thereof

    CN116617405A